LANGUAGE FUNCTIONS USED BY THE MAIN CHARACTER IN SHERLOCK HOLMES II: A GAME OF SHADOWS MOVIE - Sri Devi Arista; Sri Minda Murni (State University of Medan, 2014)
ABSTRACT This research focused on language functions used by the main character in “Sherlock Holmes” movie. The aims were to find the use of language functions and describe the dominant types of language functions used in “Sherlock Holmes” movie. The data were the dialogue of the main character in “Sherlock Holmes” movie in the first forty minutes of the movie. The research was conducted by using descriptive qualitative research. The findings show that there are six types of language functions used by the main character in “Sherlock Holmes” movie. They are expressive, directive, referential, metalinguistic, phatic, and poetic. The most dominant type of language function is metalinguistic. It means that the main character conveys code analysis by asking questions to the people so that he might invent clue for the sake of his investigation. Keyword : Language Functions, Sherlock Holmes, Movie.